CIVIL PROCEEDINGS CONCILIATIONS IN UZBEKISTAN AND KAZAKHSTAN (Journal of actual problems of jurisprudence, 2025)
This study investigates the implementation of conciliation procedures, namely, mediation, in civil justice systems of Uzbekistan and Kazakhstan case study. The two countries have adopted techniques of alternative dispute resolution (ADR) to assist them in modernizing their judicial processes, because of globalization as with their concomitant increases in caseloads. Adoption by Uzbekistan in 2018 of the Law "On Mediation" and by Kazakhstan in 2011 is a commitment to diminishing court burdens and making access to justice more accessible and enabling faster dispute resolution. It is described as a cost-effective alternative of achieving the obligation to adhere to international legal standards.The research evaluates the effectiveness of mediation practices using a comprehensive comparative legal analysis of corpus legis (including legislative text), case study analysis, and published scholarship. However, this analysis sheds light on how these dispute resolution and litigation costs were accelerated. This has been a terrific success in bringing mediation options to the public attention, but there are hurdles to be overcome -- particularly a shortage of qualified mediators in rural as well as urban areas. But nothing as effective as ADR barriers make, and he itself cannot be rolled out among the widеr range of ADR methods.The study suggests appropriate ways to tackle the existing challenges of public awareness campaign, training of mediators and legal framework for holding mediation agreement enforceable. Compared to the best practices of the world this research finds out what happened in Uzbekistan and Kazakhstan on the course of their moves to this legality and proposes ways to improve conciliation procedures to make such procedures more effective and accessible in such trаnsitioning legality.Key words: mediation, alternative dispute resolution, civil justice system, legal reform, conciliation procedures.